The Influence of Online Platforms on Decision-Making Process and Behavioural Traits of International Travelers - Abashidze, Irakli (European Scientific Journal, ESJ, 2024)
Marketing communications in the international travel and hospitality industry greatly depend on online platforms. Various goals can be achieved by using digital technologies: advertising, PR, sales, branding, customer relationship management (CRM), data analytics, and online reputation management (ORM). At the same time, international travelers actively use online channels on various stages of behaviour and decision-making process, for different purposes: pre-departure information search, evaluation of alternatives, booking and purchasing services, and post-travel actions. Besides, the peculiarities of Web 2.0 give customers wide opportunities to disseminate their reviews concerning a service. It may significantly impact potential travelers’ decisions as opinions of other customers are regarded as more reliable. Hence, digital platforms must be considered one of the central issues in tourism marketing. The importance of the issue has increased in the post-pandemic conditions when competition in the international tourism industry worldwide has moved to a new level. The paper, employing a combination of literature review, observation, and analysis of primary and secondary data, provides a discussion and comprehensive analysis of various aspects of using online platforms for marketing purposes: opportunities, decision-making process under the influence of online platforms, behaviour peculiarities of international travelers, and strategies for using online channels to increase influence efficiency. Recommendations and solutions are presented for managing various online platforms. The conclusion briefly summarizes the issues discussed in the paper.